2020
DOI: 10.1016/j.cell.2020.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Developing Covalent Protein Drugs via Proximity-Enabled Reactive Therapeutics

Abstract: Highlightsd The latent bioreactive Uaa FSY enables PD-1(FSY) to bind to PD-L1 in covalent mode d PD-1(FSY) enhances the activation of T cells and CAR-T cells more than PD-1(WT)d PD-1(FSY) inhibits tumor growth more potently than PD-1(WT) in immune-humanized mice d FSY enables an affibody to bind to the HER2 receptor on cancer cells covalently

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
140
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(168 citation statements)
references
References 58 publications
3
140
0
1
Order By: Relevance
“…Numerous antitumor agents have been reported to increase ROS production in cancer cells . Different mechanisms have been studied, such as redox cycling and mitochondrial oxidase activation . Our results indicated that the most active gold(I) complex 4 b containing an OA derivative targets TrxR to induce ROS in A2780 cells and activate ROS‐dependent ERS activation.…”
Section: Resultsmentioning
confidence: 82%
“…Numerous antitumor agents have been reported to increase ROS production in cancer cells . Different mechanisms have been studied, such as redox cycling and mitochondrial oxidase activation . Our results indicated that the most active gold(I) complex 4 b containing an OA derivative targets TrxR to induce ROS in A2780 cells and activate ROS‐dependent ERS activation.…”
Section: Resultsmentioning
confidence: 82%
“…Herein, we report the covalent nanobody-based PROTAC strategy, termed GlueTAC, for targeted membrane protein degradation with high specificity and efficiency. Relying on the recently developed proximity enabled covalent binding reaction [12][13][14][15] , we created the covalently engineered nanobody chimeras that can irreversibly bind to membrane protein targets via proximity-enabled crosslinking, while the conjugated CPP and LSS allowed the lysosomemediated target degradation (Fig. 1A).…”
Section: Main Textmentioning
confidence: 99%
“…Moreover, PDXs based on immunocompromised mice are limited in experiments of immunomodulatory compounds ( Chen and Mellman, 2017 ). Alternatively, the humanized mice, generated through transplantation of human immune cells or hematopoietic stem cells into immune-deficient mice, could reconstitute the human immunologic environment, although with challenging technique concerns ( Buque and Galluzzi, 2018 ; Li et al, 2020 ).…”
Section: Current Human-derived Models In Ocmentioning
confidence: 99%